ANALISIS IMPLEMENTASI PRINSIP-PRINSIP PSIKOLOGI KEPADA GURU SEKOLAH DASAR DALAM KURIKULUM MERDEKA BELAJAR - Dhiva Meisa Aryenda; Nadia Koesvahana, Zola Afifah, M.Jaya Adi Putra, Mauliatun Nisa (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
Basic education is a crucial foundation in shaping individuals' character and intellect. The Merdeka Curriculum, as an innovation in Indonesia's education system, provides teachers with flexibility in designing learning methods that cater to students' needs. This research aims to analyze the extent to which elementary school teachers implement psychological principles, such as motivation, cognitive development, and emotional management, within the context of the Merdeka Curriculum. The study uses a qualitative approach with a case study design, involving in-depth interviews and classroom observations. The results show that the application of psychological principles by teachers can create a more conducive and personalized learning environment, enhancing students' motivation and engagement. However, the implementation faces challenges, such as the lack of teacher training and limited learning resources. In conclusion, sustained support, including comprehensive training for teachers, is necessary to ensure the more effective and optimal implementation of psychological principles within the Merdeka Curriculum.